2008
DOI: 10.1063/1.2987706
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational energy transfer between I2(BΠu+3,ν′=21) and He at very low temperatures: Impulsive versus complex formation mechanisms assisted by tunneling through the centrifugal barrier

Abstract: The temperature dependence of the state-to-state vibrational relaxation rate constant (k(nu)(21-Delta nu)) for collisions between I(2)(B,nu(')=21) and He at very low kinetic energies was studied. The fluorescence from I(2)(B,nu(')=21-Delta nu(')) with Delta nu(')=1-5 indicates that in the temperature range of 0.6-8.2 K these states are populated by only one collision with He. The behavior of k(nu)(21-Delta nu) with temperature can be divided into two groups. The group with quantum changes Delta nu(')=1-3 shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…2 (with an increasing energy shifting) the averaged peak positions remain similar seems to be a strong indication that including the contributions of low J values still will keep a structure of peaks with similar positions to those found for J = 0. In this work we show that only j 0 o 8 are populated in the experiment, and in addition, in previous papers 30,31 it was reported that the enhancement of the collisional cross-section at the low temperatures involved in the experiment is due mainly to collisions with orbital momenta with l = 2-5. Therefore, relatively low J values are expected to contribute in the experiment.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…2 (with an increasing energy shifting) the averaged peak positions remain similar seems to be a strong indication that including the contributions of low J values still will keep a structure of peaks with similar positions to those found for J = 0. In this work we show that only j 0 o 8 are populated in the experiment, and in addition, in previous papers 30,31 it was reported that the enhancement of the collisional cross-section at the low temperatures involved in the experiment is due mainly to collisions with orbital momenta with l = 2-5. Therefore, relatively low J values are expected to contribute in the experiment.…”
Section: Resultssupporting
confidence: 78%
“…Theoretical total cross sections and partial cross sections for the Dv 0 = 0 inelastic channel Before presenting and discussing the results a comment is due. In the experimental cross sections for the I 2 (B,v 0 = 21,j 0 ) + He collisions 30,31 important contributions of total angular momenta J 4 0 are expected. Thus, the cross sections obtained from the present simulations, which are restricted to J = 0, cannot be directly compared to the experimental cross sections, since the intensities of the calculated cross sections are not converged due to the lack of J 4 0 contributions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations